EVALUASI PELAKSANAAN SASARAN KESELAMATAN PASIEN SESUAI AKREDITASI RUMAH SAKIT VERSI 2012 DI RUMAH SAKIT KHUSUS IBU DAN ANAK PKU MUHAMMADIYAH KOTAGEDE YOGYAKARTA - Totok Sundoro; Elsye Maria Rosa; Irma Risdiana (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2016)
The purpose of this study was to knowing description (policy, implementation, barriers, recommendation) on compliance efforts in patient safety goals RSKIA PKU Muhammadiyah Yogyakarta Kota Gede. Qualitative research with case study design (case study). Subjects were hospital management, the staff of the hospital and the patient. The study object is the implementation of Patient Safety Goals Hospital Accreditation Hospital In Version 2012. Policy and implementation for the implementation of 6 targets have not been fully made patient safety and well-executed yet because there are still adhere to standards that do not, do not know the rules, socialization and motivation are lacking and there is no management support. Recommendation needs to be done is the hospital management and the need to formulate a policy direction that comes with phasing as a guide to target patient safety in hospitals.